Left bundle branch pacing: An evolving site for physiological pacing - Eka P. B. Mulia (Wiley, 2021)
Abstract For patients with symptomatic bradyarrhythmia, cardiac pacing is the only appropriate treatment option. Electrical and mechanical dyssynchrony caused by traditional right ventricular apical pacing leads to left ventricular dysfunction and atrial arrhythmias. Physiological pacing stimulates natural cardiac conduction, resulting in synchronized ventricular contraction. Even if His bundle pacing (HBP) is an ideal physiological pacing modality, it is technically not always feasible because of high capture thresholds, disease in the distal His bundle, and follow‐up troubleshooting issues. Left bundle branch pacing (LBBP) has been proposed as a viable alternative to HBP since it provides lead stability, a low and stable pacing threshold, and correction of distal conduction system disease.